Total and Bioavailable Arsenic Concentration in Arid Soils and Its Uptake by Native Plants from the Pre-Andean Zones in Chile - Diaz-Schulze, O; Pastene-Olivares, R; Pastene-Olivares, R (2011)
Arsenic is the most important contaminant of the environment in northern Chile. Soil samples and plant organs from three native plant species, Pluchea absinthioides, Atriplex atacamensis and Lupinus microcarpus, were collected from arid zones in order to determine the total and bioavailable arsenic concentrations in soils and to assess the bioconcentration factor (BCF) and transport index (Ti) of arsenic in the plants. Total arsenic concentrations in soils (pH 8.3-8.5) where A. atacamensis and P. absinthioides were collected, reached levels considered to be contaminated (54.3 ± 15.4 and 52.9 ± 9.9 mg kg -1, respectively), and these values were approximately ten times higher than in soils (pH 7.6) where L. microcarpus was collected. Bioavailable arsenic ranged from 0.18 to 0.42% of total arsenic concentration. In the three plant species, arsenic concentration in leaves were significantly (p ? 0.05) higher than in roots. L. microcarpus showed the highest arsenic concentration in its leaves (9.7 ± 1.6 mg kg -1) and higher values of BCF (1.8) and Ti (6.1), indicating that this species has a greater capacity to accumulate and translocate the metalloid to the leaf than do the other species. © 2011 Springer Science+Business Media, LLC.